Restoring the Coherence of Quantum Emitters through Optically Driven Motional Narrowing Forces - Pont, Mathias; Phaneuf-L’Heureux, Anne-Laurence; André, Régis; Francoeur, Sébastien (Nano letters, 2021)
Motional narrowing is a phenomenon by which a quantum state can be entangled with a noisy environment and still retain its intrinsic coherence. Using two optically induced motional forces driving the environmental electrical field amplitude and fluctuations, we present a compelling illustration of the effects of motional narrowing on the energy, line shape, and line width of a single quantum emitter, a Te2 molecule embedded in ZnSe, subject to spectral diffusion. Motional narrowing is achieved in several regimes, irrespectively of the inhomogeneous disorder initially present and the charge reservoir state sourcing the field. The optimal coherence limit set by the radiative rate can be approached by accelerating spectral diffusion into the THz regime. Motional narrowing applies to any quantum systems for which environmental fluctuations can be deliberately accelerated and alleviates the need for perfected materials and devices.